Experience in the use of olaparib poly (ADP-ribose) polymerase inhibitors in maintenance therapy of BRCA-associated ovarian cancer - V. N. Zhurman; V. M. Nechushkina (Сибирский онкологический журнал, 2023)
Aim to study the frequency of BRCA1/2 gene mutations , the efficacy of ovarian cancer therapy depending on the presence of BRCA1/2 mutations as well as the efficacy of olaparib maintenance therapy in BRCAassociated ovarian cancer.Material and Methods. The retrospective analysis included 355 patients with high-grade, stage I–IV serous ovarian cancer. The examination for a mutation in the BRCA1/2 gene was carried out within the framework of the program “Improvement of molecular genetic diagnostics in the Russian Federation in order to increase the effectiveness of antitumor treatment”.Results. Mutations in the BRCA1/2 genes were detected in 98 out of 355 (27.6 %) patients. Mutations of the BRCA1+ gene were detected in 62 out of 230 patients with ovarian cancer of stages IIIC–IV (27.0 %), the BRCA2 gene – in 9 out of 230 (3.9 %). In ovarian cancer of stages III–IV, BRCA gene mutations were absent in 159 of 230 (69.1 %) patients. The median time to progression in stages III–IV of the disease with a mutation in the BRCA1 gene was 22.0 months, in the BRCA2 gene – 27.0 months, in patients without mutations in the BRCA1/2 genes – 17.0 months, median life expectancy – 70.0; 65.0 and 45.0 months, respectively. Patients with serous ovarian carcinoma of high-grade I–IV stages with the presence of mutations in the BRCA1/2 genes were divided into two groups. The first group (6 out of 26 patients, 23.1 %) consisted of patients with stage IIIC–IV high-grade serous ovarian carcinoma, who received olaparib as maintenance therapy after the 1st line of chemotherapy, the second group (20 out of 26 patients, 76.9 %) were patients with stage I–IV high-grade serous ovarian carcinoma, who received olaparib in maintenance mode after 2 or more lines of chemotherapy.Conclusion. The presence of BRCA1/2 gene mutations significantly increased the median life expectancy of patients with stage IIIC–IV serous ovarian cancer, and primary cytoreduction significantly improved both overall survival and survival to progression in this group of patients. Maintenance therapy with olaparib is more appropriate after the 1st line of treatment than after subsequent ones.